# How to derive the permittivity conductivity relation?

I would like to derive the common (and important - to me atleast) equation:

$$\epsilon = \epsilon_a + j\frac{\sigma}{\omega\epsilon}$$

I have seen some resources calling this a definition (in which case, it may not have a derivation), but it looks like it definitely should and it should fall out of Maxwell's equations, but I cannot do it!

So, starting with,

$$\nabla \times \vec{H} = j\omega\vec{D}+\vec{J}$$

and using Ohm's law and a constitutive relation, which for convenience is:

$$\vec{J} = \sigma \vec{E}$$ and $$\vec{D} = \epsilon\vec{E}$$

One can arrive at:

$$\nabla \times \vec{H} = j\omega\epsilon\vec{E}+\sigma\vec{E}$$ (Eq. 1)

Keeping the above in mind for a moment and working on this:

$$\nabla \times \vec{E} = -j\omega\mu\vec{H}$$

one can take the curl of both sides:

$$\nabla \times (\nabla \times \vec{E}) = -j\omega\mu\nabla \times \vec{H}$$

Using the vector identity $$\nabla \times (\nabla \times \vec{A}) = (\nabla(\nabla\cdot\vec{A})-\nabla^2 \vec{A})$$, recalling Eq. 1 and noting that for a region without a source $$\nabla\cdot\vec{E} = 0$$, the above becomes:

$$\nabla^2\vec{E}=-\omega^2\epsilon\mu\vec{E}+j\omega\mu\sigma\vec{E}=0$$

$$\nabla^2\vec{E}+\omega^2\epsilon\mu\vec{E}(1-j\frac{\sigma}{\omega\epsilon})=0$$

This wave equation for a lossy material is as far as I can get...

• magnetic permeability is often taken $\mu=1$ in these situations of non-magnetic materials Jan 17, 2020 at 15:30
• @Simon thank you. That solves one problem... but the rest is still puzzling me. Jan 17, 2020 at 17:06

It is actually just the rhs of one of the Maxwell's equations $$\nabla\times\mathbf{H}=\mathbf{J}+\frac{\partial \mathbf{D}}{\partial t}.$$ If we perform Fourier transform in time (or simply take $$\mathbf{H},\mathbf{J},\mathbf{D},\mathbf{E}\propto e^{j\omega t}$$) then $$\nabla\times\mathbf{H}(\omega)=\mathbf{J}(\omega)-j\omega \mathbf{D}(\omega) = \sigma \mathbf{E}(\omega)-j\omega \epsilon\mathbf{E}(\omega)=\\-j\omega\left(\frac{\sigma}{-j\omega}+\epsilon\right)\mathbf{E}(\omega)=-j\omega\epsilon_{eff}\mathbf{E}(\omega)=-j\omega\mathbf{D}_{eff}(\omega),$$ where the effective permittivity is introduced in analogy with $$\mathbf{D}=\epsilon\mathbf{E}$$.

It could be also be generalized to frequency dependent conductance and permittivity, taking the correct real-time relation between the quantities: $$\mathbf{J}(\omega)=\sigma(\omega)\mathbf{E}(\omega)\Leftrightarrow \mathbf{J}(t)=\int_{-\infty}^tdt'\sigma(t-t')\mathbf{E}(t'),\\ \mathbf{D}(\omega)=\epsilon(\omega)\mathbf{E}(\omega)\Leftrightarrow \mathbf{D}(t)=\int_{-\infty}^tdt'\epsilon(t-t')\mathbf{E}(t')$$

Let's define a new wave equation that electric field will be subject to. In phasor notation we have $$\frac{\partial}{\partial t}\to j\omega$$, which gives us $$\nabla^2\vec{E}+\omega^2\frac{1}{v^2}\vec{E}=0$$

We can compare this to your last equation which read $$\nabla^2\vec{E}+\omega^2\epsilon\mu\vec{E}(1-j\frac{\sigma}{\omega\epsilon})=0$$ $$\nabla^2\vec{E}+\omega^2\epsilon\mu\vec{E}(1-j\frac{\sigma}{\omega\epsilon})=0=\nabla^2\vec{E}+\omega^2\frac{1}{v^2}\vec{E}$$ $$\implies \omega^2\epsilon\mu\vec{E}(1-j\frac{\sigma}{\omega\epsilon})-\omega^2\frac{1}{v^2}\vec{E}=0$$ $$\implies \omega^2 (\epsilon\mu-j\frac{\sigma\mu}{\omega}-\frac{1}{v^2}) \vec E=0 \implies \epsilon\mu-j\frac{\sigma\mu}{\omega}-\frac{1}{v^2}=0$$

Normally, we would have $$v^2=\frac{1}{\epsilon\mu}$$. We can still define effective dielectric and magnetic constants to reflect the characteristics of this system. As it is usual, we set $$\mu_{eff}=\mu$$ since magnetic effects are usually ignored in these settings, $$\epsilon\mu-j\frac{\sigma\mu}{\omega}=\epsilon_{eff}\mu_{eff}=\epsilon_{eff}\mu$$ $$\implies \boxed{\epsilon_{eff} = \epsilon-j\frac{\sigma}{\omega}}$$

First, this doesn't match exactly your formula in the beginning, however the Wikipedia page actually has this result.

I actually don't know if in free space $$\sigma\ne0$$ results in any other behavior than the "lossy" EM wave propagation. But if that's all, this assumption accurately models the system (since the wave equations are of correct shape).

• Thanks for your reply. This isn't really what I was looking for. This isn't a derivation. Would it be possible to add some more steps? Also, it looks like you've squared $v$ to get $\epsilon$ and $\mu_a$ in the numerator. You then cancel $\mu_a$ with $\mu_a$ in the denominator. If squaring $v$ makes $\epsilon$, not $\epsilon_a$, why does it make $\mu_a$ and not $\mu$?! The final form of your derivation is not the same as the equation I wanted to arrive at. Jan 17, 2020 at 17:22
• Yeah there are a few mistakes I am trying to resolve. Though the "derivation" depends on defining a effective refractive index to the material so that it still follows Maxwell's equations in a reasonable way. I'll try to improve this. Jan 17, 2020 at 17:25
• Thank you! I appreciate that. Jan 17, 2020 at 17:26
• There’s an issue in the answer relating the second derivative in time to $j\omega$. It should be the first derivative in time corresponding to $j\omega$. Jan 30, 2022 at 4:25
• @Newbie That's a (thankfully) simple typo and doesn't affect the rest of the answer. I'll fix it now. Jan 30, 2022 at 18:35